2007
DOI: 10.1002/hyp.6887
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variability in riverine dissolved organic matter composition determined by in situ optical measurement in the San Joaquin River (California, USA)

Abstract: Abstract:Dissolved organic matter (DOM) concentration and composition in riverine and stream systems are known to vary with hydrological and productivity cycles over the annual and interannual time scales. Rivers are commonly perceived as homogeneous with respect to DOM concentration and composition, particularly under steady flow conditions over short time periods. However, few studies have evaluated the impact of short term variability (<1 day) on DOM dynamics. This study examined whether diurnal processes m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
122
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 163 publications
(130 citation statements)
references
References 63 publications
7
122
1
Order By: Relevance
“…In contrast, photochemical degradation of DOC [e.g., Spencer et al, 2007;Lu et al, 2013] is unlikely to have had a substantial impact on diel DOC dynamics because the stream channel was incised and shaded by riparian vegetation for much of its length.…”
Section: Temporal Dynamics Of Streamflow No 3 -N and Docmentioning
confidence: 99%
“…In contrast, photochemical degradation of DOC [e.g., Spencer et al, 2007;Lu et al, 2013] is unlikely to have had a substantial impact on diel DOC dynamics because the stream channel was incised and shaded by riparian vegetation for much of its length.…”
Section: Temporal Dynamics Of Streamflow No 3 -N and Docmentioning
confidence: 99%
“…Diel patterns in DOC, especially the labile fraction associated with PER, are difficult to measure because of rapid uptake in the plankton and because the signal is so small relative to higher background DOC concentrations. Although overnight drawdown in DOC has been documented in lotic (Spencer et al 2007) and productive marine (Johnson et al Fig. 6.…”
Section: Water Characteristics Nmentioning
confidence: 99%
“…DOM composition was examined using a suite of chromophoric dissolved organic matter (CDOM) parameters that can be linked to molecular weight and aromaticity [Helms et al, 2008;Spencer et al, 2012]. Since several CDOM parameters can be measured in situ at a high temporal resolution [Spencer et al, 2007a[Spencer et al, , 2007bPellerin et al, 2012], a further aim of this study was to assess the utility of different parameters for tracking DOC export and DOM composition in impounded systems. Specifically, this work will help inform restoration activities associated with removal of the four lower dams on Klamath River (Oregon/California, USA) scheduled for the next decade.…”
Section: Seasonal and Impoundment Effects On Dom 1946mentioning
confidence: 99%
“…The spectral slope (S) parameter varies with CDOM source and biological and photochemical processes that lead to changes in molecular weight or aromaticity [Spencer et al, 2007a[Spencer et al, , 2007bHelms et al, 2008]. Spectral slope values were calculated for wavelength ranges 275-295 nm (S 275-295 ) and 350-400 nm (S 350-400 ) as previous studies have shown that these wavelength ranges are sensitive to changes in the chemical composition of CDOM and track processes that differentially influence S [Helms et al, 2008].…”
Section: Sample Collection and Processingmentioning
confidence: 99%